Deteksi Pola Sebaran Tumpahan Minyak (Oil Spill) Menggunakan Citra Sentinel-1A di Perairan Karawang - Fernanda Nadia Damayanti; I Dewa Nyoman Nurweda Putra; I Wayan Nuarsa; Maryani Hartuti (Journal of Marine and Aquatic Sciences, 2022)
In recent years, oil spill accidents very often occur due to the development of sea transportation and oil exploitation. Increased exploitation of oil resources is a concern for oil spills that are very harmful to marine ecosystems. On July 12 2019, there was a well kick in the well reactivation YYA-1 owned by PT. Pertamina Hulu Energi work area Offshore North West Java (ONWJ) in Karawang Sea. The oil spill were spread up to Banten and continued to spread widely. Remote sensing is one of the methods that can be used to detect and monitor the oil spill by quickly viewing the location and spill points, and the pace and direction of the oil that can be utilized for cleaning. This research aims to determine the detection of oil spill using Sentinel-1A imagery and to determine oil spill patterns in Karawang Sea before spills occur until the well YYA-1 was closed that was on October 7 2019. This detection is done with adaptive threshold algorithm through Sentinel applications platform (SNAP). The results showed that oil spill has a trajectory spread pattern at the beginning of the spill which occur on July 18 2019. After July 18th, the spread pattern turned random and interrupted the spreading process. The spread has an estimated spread area of 145.85 km2. The spread of oil spill moved towards the northwest to the west approaching the coast and further away from the source of the spill, to Pandjang Island, Banten.